The fecundity of Hilsa ilisha from the river Padma near Godagari of Rajshahi district - Akter, Mst Arifa; Hossain, MD; Hossain, M Kabil; Afza, R; Bhuyian, AS (University Journal of Zoology, Rajshahi University, 2008)
The fecundity of Hilsa ilisha (Hamilton, 1822) were estimated from 20 fully matured females caught from the Padma river near Godagari, Rajshahi and collected from different fish market of Rajshahi City from June to October 2002. The fecundity (F) was found to vary from 5,58,700 to 18,67,000, mean 1239360.35 ± 405068.97 for the fishes with 350-557mm in total length and mean 455.25± 59.94mm and with 600 -1775g in total body weight and mean 1181.85± 356.12g. The co-efficient of correlation for F/TL, F/TW, F/GL and F/GW were 0.8036, 0.8853, 0.7606 and 0.7922 respectively. The regression line for the TL, TW, GL and GW of the sample fishes were found to be linear when they were plotted against their fecundity. All the variables observed (P<0.05) where highly significant . The best indicator of the fecundity of H. ilisha was found to be the total body weight. Key words: Fecundity, gonad, GSI, Hilsa ilisha. Univ. j. zool. Rajshahi Univ. Vol. 26, 2007. pp. 41-44